Improved S-bend optical waveguide loss formula verified by experiments - Ary Syahriar (Scientific Reports)
Abstract Curvature of a dielectric waveguide always leads to attenuation of the mode power as it propagates through the curved region. In single mode guides, bending loss becomes significant as the radius of curvature reduces and is strongly dependent on the confinement of the guided mode, so that weakly guiding waveguides can tolerate only large radii of curvature. In this paper we verify our new theoretical version on power loss prediction of S-bend optical waveguides by using analytical theory based on integration of absorption coefficient and compare it to the experimental measurement of such waveguide bends. The objectives are to formulate the best analytical theory available that can predict the power loss in S-bends whose shape is defined as a function y = f(x), where its first derivative is continuous. Using this technique, the effect of post-process thermal annealing of channel guide devices fabricated by electron beam irradiation of silica PECVD materials is investigated. A particular performance characteristic is examined, which have its origin in the index reduction caused by annealing, increases in waveguide bend losses. Furthermore, to determine the waveguide shape, we used Marcatili’s effective index method, employing model-dependent parameters obtained from the experimental data.